2021
DOI: 10.3389/fmicb.2021.725391
|View full text |Cite
|
Sign up to set email alerts
|

In silico Evolution and Comparative Genomic Analysis of IncX3 Plasmids Isolated From China Over Ten Years

Abstract: IncX3 plasmids are correlated with the dissemination and acquisition of carbapenem resistance in Enterobacteriaceae and have been prevalent in China over the last 10 years. Since the distribution characteristics of IncX3 plasmids across China as well as their evolutionary traits for 10 years remain unclear, here we conducted a retrospective literature review and in silico comparative analysis of IncX3 plasmids in publicly available IncX3 plasmid genomes. IncX3 plasmids distributed in 17 provinces or cities wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The core genes are shared among the three typical completely sequenced IncX3 plasmids (pEC13_35, pIncX-SHV, and pNDM-HN380): replication (replication initiation protein, pir ; replication accessory protein, bis ), partitioning ( parA and parB ), plasmid maintenance (a putative DNA-binding protein, hns ; a putative type III topoisomerase, topB ), conjugation/type IV secretion system (T4SS, with 11 genes, pilX1 to pilX11 ), transcriptional activator ( actX ), and putative DNA transfer proteins ( taxA and taxC ) ( Ho et al, 2012 ). A retrospective analysis of IncX3 in China shows that the IncX3 plasmid backbone has been highly conserved over the past decade ( Liu et al, 2021a ). The accessory module mainly includes transposase genes, metabolic functions related genes, and antimicrobial resistance encoding genes.…”
Section: Structural Characteristics Of Incx3 Plasmidsmentioning
confidence: 99%
“…The core genes are shared among the three typical completely sequenced IncX3 plasmids (pEC13_35, pIncX-SHV, and pNDM-HN380): replication (replication initiation protein, pir ; replication accessory protein, bis ), partitioning ( parA and parB ), plasmid maintenance (a putative DNA-binding protein, hns ; a putative type III topoisomerase, topB ), conjugation/type IV secretion system (T4SS, with 11 genes, pilX1 to pilX11 ), transcriptional activator ( actX ), and putative DNA transfer proteins ( taxA and taxC ) ( Ho et al, 2012 ). A retrospective analysis of IncX3 in China shows that the IncX3 plasmid backbone has been highly conserved over the past decade ( Liu et al, 2021a ). The accessory module mainly includes transposase genes, metabolic functions related genes, and antimicrobial resistance encoding genes.…”
Section: Structural Characteristics Of Incx3 Plasmidsmentioning
confidence: 99%
“…In addition, other bla NDM variants carried on IncX3 plasmids, namely, bla NDM-17 , bla NDM-19 , bla NDM-20 , bla NDM-21 , and bla NDM-33 , have been reported ( 9 13 ). The role of the IncX3 plasmid in mediating the dissemination of bla NDM has therefore been considered ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, there have been no studies on the relationship between specific genetic conflicts and the fitness cost of carrying ndm /IncX3 plasmids. Our work has previously revealed that the ndm /IncX3 plasmids are highly conserved [ 9 ], and thus we suggest that specific genetic conflicts that may occur in the host chromosome confer a diverse fitness cost.…”
Section: Introductionmentioning
confidence: 79%
“…However, some studies have also reported high fitness costs [ 12 , 13 ], though the variety of fitness costs and the mechanism involved remain unclear. Our group has been exploring IncX3 plasmid prevalence for several years [ 8 , 9 , 19 ]. In the present study, we found that the ndm /IncX3 plasmid led to an elevated fitness cost in the C600 strain, for which specific genetic conflicts were responsible and related to SNPs in genes of the cell membrane and sugar metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation